EVALUATION OF SLEEP QUALITY WITH BURNOUT LEVEL IN EMERGENCY MEDICAL ASSISTANTS - Dilek Atik (Rojan GÜMÜŞ, 2020)
Burnout syndrome is a condition in which people working in businesses that require face-to-face communication, with prolonged stress where personal coping methods fail. Healthcare professionals are one of the most risky occupational groups in terms of burnout syndrome due to their heavy workload. In addition to the workload, the need to provide emotional support, providing care for severe and deadly patients, disturbed sleep patterns, and the high number of duties increase burnout in major stressors on healthcare professionals. In this study, our primary aim is to evaluate the relationship between burnout level and sleep quality in emergency medicine assistants. This study is a descriptive and cross-sectional study. According to the data obtained from the Higher Education Board, the personal information form and maslach burnout scale and pitsburg sleep quality scale surveys were sent to all Burnout syndrome is a condition in which people working in businesses that require face-to-face communication, with prolonged stress where personal coping methods fail. Healthcare professionals are one of the most risky occupational groups in terms of burnout syndrome due to their heavy workload. In addition to the workload, the need to provide emotional support, providing care for severe and deadly patients, disturbed sleep patterns, and the high number of duties increase burnout in major stressors on healthcare professionals. In this study, our primary aim is to evaluate the relationship between burnout level and sleep quality in emergency medicine assistants. This study is a descriptive and cross-sectional study. According to the data obtained from the Higher Education Board, the personal information form and maslach burnout scale and pitsburg sleep quality scale surveys were sent to all emergency assistants receiving training in Turkey. A total of 94 people working as emergency medical assistants participated in our study. According to the maclach burnout scale subgroup emotional exhaustion, 84% (n= 79) of the participants had a high level of emotional exhaustion and 16% (15) had moderate emotional exhaustion. When the MBI subgroup desensitization was evaluated, 87.2% (n= 82) was found high and 12.8% (n= 12) was found moderate. When the personal success of the MBI subgroup was evaluated, 97.9% (n= 92) was found low and 2.1% (n= 2) was found moderate. When the correlation between the MBI subgroups and the PSQS scoring was evaluated, a moderate positive correlation was found between emotional exhaustion and PSQS (p≤0.001). When the sleep quality with MBI is evaluated by regression analysis, it is seen that the state of exhaustion affects quality of sleep by 13.1%. High level of burnout during the education period of the emergency medicine assistant causes sleep quality deterioration. This situation causes difficulties in business and private life over time. We think that it will be beneficial to regulate the monthly working hours in order to decrease the burnout levels and increase sleep quality for keeping EMAs physically and mentally healthy, to increase the training staff to make them feel safe, and to organize programs to increase non-work social activities.